The Impact of a Manufacturing Process on the Stability of Microcrystalline Long-Acting Injections: A Case Study on Aripiprazole Monohydrate - Tomasz Pietrzak; Ziemowit Szendzielorz; Joanna Borychowska; Tomasz Ratajczak; Marcin Kubisiak (Pharmaceutics)
Background/Objectives: Long-acting injections (LAIs) are innovative drug delivery systems that improve patient compliance by maintaining therapeutic drug levels over extended periods. Micro- and nanosuspensions are commonly used in LAIs to enhance bioavailability, but their thermodynamic instability poses challenges, including particle aggregation and growth. This study aimed to evaluate the impact of two helping processes—vehicle thermal treatment and high-shear homogenization—on the stability and manufacturing efficiency of aripiprazole monohydrate (AM) suspensions. Methods: AM suspensions containing sodium carboxymethyl cellulose (CMCNa), mannitol and disodium phosphate in water for injections (WFIs) were prepared using a combination of thermal treatment of the vehicle solution, high-shear homogenization and bead milling. Four manufacturing variants were tested to assess the influence of these processes on particle size distribution (PSD), viscosity and stability during a 3-month accelerated stability study. Molecular weight changes in CMCNa from thermal treatment were analyzed using size exclusion chromatography with multiangle scattering (SEC-MALS), and PSD was measured using laser diffraction. Results: Thermal treatment of the vehicle solution had minimal impact on CMCNa molecular weight, preserving its functionality. High-shear homogenization during bead milling significantly reduced particle aggregation, resulting in improved PSD and reduced viscosity. Synergistic effects of the two helping processes used in one manufacturing process were observed, which led to superior stability and minimal changes in PSD and viscosity during storage. Batches without the helping processes exhibited increased particle size and viscosity over time, indicating reduced suspension stability. Conclusions: Incorporating vehicle thermal treatment and high-shear homogenization during bead milling enhances the stability and manufacturing efficiency of AM suspensions. These findings underscore the importance of optimizing laboratory-scale processes to ensure the quality and safety of pharmaceutical suspensions.